Enantioselective synthesis of decarestrictine J - Chowdhury, Partha Sarathi; Gupta, Priti; Kumar, Pradeep (Tetrahedron Letters, 2009)
An efficient total synthesis of decarestrictine J has been achieved using ring-closing metathesis and Yamaguchi esterification as key steps. The stereogenic centres were generated by means of iterative hydrolytic kinetic resolution (HKR) of racemic epoxides. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Decanolides; epoxides; Hydrolytic kinetic resolution; Ring-closing metathesis; Yamaguchi esterification

First asymmetric total synthesis of aspinolide A - Chowdhury, Partha Sarathi; Gupta, Priti; Kumar, Pradeep (Tetrahedron Letters, 2009)
The first total synthesis of aspinolide A has been achieved using ring-closing metathesis as a key step. The stereogenic centers were generated by means of hydrolytic kinetic resolution (HKR) of racemic epoxides. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Decanolides; epoxides; Hydrolytic kinetic resolution; Ring-closing metathesis

Desymmetrization approach to the enantiopure syn/anti-1,5-diols via hydrolytic kinetic resolution (hkr) of functionalized meso-bis-epoxides: further elaboration to syn/syn-1,3,5-triols and application to the formal synthesis of cryptocarya diacetate - Kumar, Pradeep; Chowdhury, Partha Sarathi; Pandey, Menaka (Advanced Synthesis & Catalysis, 2013)
A new approach has been developed for the synthesis of enantiopure syn/anti-1,5-diols by desymmetrization of functionalized meso-bis-epoxides using hydrolytic kinetic resolution (HKR). The usage of this protocol was demonstrated by converting syn-1,5-diols into syn/syn-1,3,5-triols and its subseqent application to the formal synthesis of cryptocarya diacetate.
Keywords: bis-epoxides; cryptocarya diacetate; desymmetrization; stereoselective reduction; synthetic methods

Highly concise and practical route to clavaminols, sphinganine and (+)-spisulosine via indium mediated allylation of alpha-hydrazino aldehyde and a theoretical insight into the stereochemical aspects of the reaction - Pandey, Menaka; Chowdhury, Partha Sarathi; Dutta, Achintya Kumar; Kumar, Pradeep; Pal, Sourav (RSC Advances, 2013)
A conceptually different approach has been employed for the synthesis of 1,2-amino alcohols by proline-catalyzed alpha-amination of aldehyde and one-pot indium mediated allylation of the crude alpha-hydrazino aldehydes. DFT based quantum chemical calculations have been performed to obtain a quantitative explanation of the stereoselectivity of the reaction.

Total synthesis of umuravumbolide and hyptolide through silicon-tethered ring-closing metathesis - Chowdhury, Partha Sarathi; Kumar, Pradeep (European Journal of Organic Chemistry, 2013)
The total synthesis of umuravumbolide and hyptolide has been achieved in a efficient manner by using temporary silicon-tethered ring-closing metathesis and cross-coupling reactions as key steps. The stereogenic centres were generated by means of proline-catalysed -aminoxylation of aldehydes and Brown's asymmetric allylation method.
Keywords: lactones; Metathesis; Silanes; synthetic methods; Total synthesis; Wittig reactions